Il lavoro nella Costituzione - Pascucci, Paolo (Cultura giuridica e diritto vivente, 2016)
[The Work in the Constitution] The report analyzes the importance that the work assumes in the Italian Constitution of 1948, as a cornerstone of democracy and as a tool of dignity and empowerment of the citizen. After having reviewed the main provisions of the Constitution dealing with the work, the rights of workers and trade unions, the report focuses on structural changes affecting the work today, trying to verify the actuality of the constitutional provisions.